The Missngs of Arabic Dictionary in The book of "Attaaliqat wa- al-nawadir" By Abu Ali Al-Hajari (The International Journal for Scientific Research, 2023)
This study deals with the verbal and semantic defects of the Arabic lexicon, which were monitored "Attaaliqat wa- al-nawadir" By Abu Ali Al-Hajari, and shows its impact on Arabic dictionaries after him in terms of monitoring this linguistic richness that they missed.  It is known that the collection of missing items is of great importance in contributing to the completion of our ancient linguistic dictionaries, filling the gaps in them and enriching their content. It contributes to reviving a root described as neglected, or helps to understand an ancient text or witness.  The study concluded with results, including: The book of "Attaaliqat wa- al-nawadir" By Abu Ali Al-Hajari is a source full of lexical gaps that are not few.  The diversity of the Arabs' environments and their different lifestyles also led to the multiplicity of the semantics of the words.  Highlighting the lexical missing helps to complete the Arabic lexicon material and contributes to building the desired historical lexicon and Arabic linguistic atlas.
Keywords: missed; lexicon; Effect; Verbal; Semantic